Critical Reassessment: The European Cloud University Platform and New Challenges of the Quartet Helix Collaboration in the European University System - Kaivo-oja Jari; Stenvall Jari (KAUNO TECHNOLOGIJOS UNIV, 2022)
The European Commission has presented how it intends to give Europe a lead in the data-driven economy by enabling cloud-based services and world-class infrastructures for industry, scientists, and public services. In 2011 we discussed and proposed the cloud university platform for the European Union in the European Inte-gration Studies. The purpose of the study is to deliver a critical reassessment of the European Cloud University Platform. Today a new European Open Science Cloud (EOSC) will offer Europe's 1.7 million researchers and 70 million science and technology professionals a virtual environment to store, share and re-use the large vol-umes of information generated by the big data revolution. The EOSC will be underpinned by the European Data Infrastructure, deploying the high-bandwidth networks and super-computer capacity necessary to effectively access and process large datasets stored in the cloud. There is also a target to build a single market for the Internet of Things: with the right standards for interoperability, and open cross-sector platforms for IoT devices and services to connect seamlessly, and scale-up, up anywhere in the EU. Our assessment is focused on the European Open Science Cloud (EOSC) and its operational functioning and implementation process. The study is based on conventional assessment methods and tools. The methodology is a mostly mixed methodology (with both qualitative and quantitative data analytics) and it pays attention to argumentation logic and actual policy planning process and operational implementation of the EOSC.
The role of Research Infrastructures (RIs), as well as cross-border innovation management approach are emphasized in recent transnational European research and innovation policy. Support for RIs form important pillars in the Horizon 2020-framework, as well as in the Horizon Europe-framework based on the idea that modern science requires unique global competitive capabilities, which individual institutions, or even individu-al European countries, often cannot provide by themselves. There are very good reasons to perform a critical assessment, because according to the European Cloud Initiative, over the coming 5 years, the European Com-mission will put forward proposals to meet the euro 4.7 billion investment need to integrate and consolidate data infrastructure. These vital proposals will bring together the EU and other sources, including Member States and private investments. By 2017, all scientific data produced by projects under the euro 77 billion within the Hori-zon 2020 research and innovation programme will become open by default to ensure that the scientific com-munity can re-use the enormous amount of data they generate. This change is not marginal and needs more reflective discussions. The primary database of reassessment is the documents of the European Open Science Cloud (EOSC) and (1) associated European Commission work programme (overview of institution-wide deliv-erables), (2) the strategic plan (department strategy, objectives for 2016-2020) and (3) other EU management plans and scientific discussion associated with platform economy research. These EU documents were pub-lished after our original EIS article.
The key results of critical reassessment are: (1) There are concrete needs to strengthen links between the European Open Science Cloud, Industry 4.0 strategy and Industry 4.0 Curriculum in Europe, (2) the concept of platform needs more discussion in the future developments of the European Open Science Cloud (EOSC), (3) country-level university and research community participation in the EOSC requires more discussion and more updated operational implementation plans and programs, and (4) there is need to plan symbiotic dig-italized innovation eco-system policy and economic growth policy framework for the European Union. We summarise our critical reassessment with a critical note that there are big integration challenges of the Eu-ropean Open Science Cloud.